Database Management Systems (Texas Journal of Multidisciplinary Studies, 2022)
A database management system is a software system designed to create a common database on a computer for many applications, to keep it up-to-date, and to ensure that users can use the information in it effectively within the authority given to them. A database is equally necessary to create and maintain a database of an information system.